State Islamic School: Institutional Transformation of Islamic Religious Education at SMP Negeri 3 Dempet in Demak Regency - Edi Kuswanto; Rahmat Hariyadi; Sutrisno Sutrisno; Fatihah Fajar Sari; Suharsono Suharsono (Program Studi Pendidikan Agama Islam, 2022)
The research focused on the institutional transformation of Islamic religious education (PAI) in SMP Negeri 3 Dempet, Demak Regency. The purpose of the study was to determine the form of PAI institutional transformation at SMP Negeri 3 Dempet in Demak Regency, the design of the state Islamic school as a form of PAI institutional transformation, and the contribution of PAI institutional transformation to the academic quality of PAI. Methods of data collection were interviews, field observations, and documentation. Data were obtained from the principal, school committee, vice principal, PAI teacher, education staff, and students, with 30 respondents. The data were then analyzed using an interactive analysis model with the stages of data collection, data reduction, data presentation, and verification/conclusion. The study results revealed that 1) state Islamic school is a form of PAI institutional transformation at SMP Negeri 3 Dempet, Demak Regency, 2) state Islamic school was built through intracurricular, extracurricular, and co-curricular activities, and 3) to improve academic quality, the institutional transformation of PAI in SMP Negeri 3 Dempet, Demak Regency, was conducted through regular programs, regular tahfidz (memorization) programs, and tahfidz boarding programs. This research contributes to the finding of the state Islamic school as a model for PAI's institutional transformation in schools.